2007
DOI: 10.1007/s00441-007-0403-9
|View full text |Cite
|
Sign up to set email alerts
|

Balbiani cytoplasm in oocytes of a primitive fish, the sturgeon Acipenser gueldenstaedtii, and its potential homology to the Balbiani body (mitochondrial cloud) of Xenopus laevis oocytes

Abstract: The oocytes of many organisms, including frogs and fish, contain a distinct cytoplasmic organelle called the Balbiani body. Because of the scarcity of published information and the tremendous variability in the appearance, ultrastructure, and composition of Balbiani bodies between species, the function of the Balbiani body and its inter-species homology remain a mystery. In Xenopus laevis, the Balbiani body is known to play a role in transporting germ cell determinants and localized RNAs to the oocyte vegetal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 27 publications
2
61
0
Order By: Relevance
“…This agrees with the recent identification of ovarian buc in the Chinese sturgeon ( Acipenser sinensis ) representing the primitive Acipenseriformes with estimated origin time about 390 mya [37, 38]. The Balbiani body and specification pattern of the sturgeon PGCs were shown to closely resemble that of anurans, and injected zebrafish Buc-GFP accumulated at the cleavage furrows similar to our salmon study [39, 40]. Together with the localization of sturgeon dazl in the Balbiani body [41], the results suggest the involvement of Buc in the germ plasm assembly of this basal ray-finned fish.…”
Section: Discussionsupporting
confidence: 91%
“…This agrees with the recent identification of ovarian buc in the Chinese sturgeon ( Acipenser sinensis ) representing the primitive Acipenseriformes with estimated origin time about 390 mya [37, 38]. The Balbiani body and specification pattern of the sturgeon PGCs were shown to closely resemble that of anurans, and injected zebrafish Buc-GFP accumulated at the cleavage furrows similar to our salmon study [39, 40]. Together with the localization of sturgeon dazl in the Balbiani body [41], the results suggest the involvement of Buc in the germ plasm assembly of this basal ray-finned fish.…”
Section: Discussionsupporting
confidence: 91%
“…The Chinese sturgeon BB/MC, however, seems to diffuse in the cytoplasm of early developing oocytes by in situ hybridization and MitoTracker staining, similar to the Russian sturgeon BB/ MC distribution at stage II and stage III, while the Russian sturgeon BB/MC is concentrated around the germinal vesicle at stage I. There was little difference in the characterization of BB/MC distribution in Russian and Chinese sturgeon, because the antisense probes taken by Zelazowska et al (2007) belonged to Drosophila and Xenopus, not itself and were hydrolyzed to fragments of 20-50 bp, which would include much non-specific hybridization, resulting in abundant germ plasm RNA concentrated around the germinal vesicle. In summary, based on in situ hybridization of germ plasm RNA, dazl and colocalization MitoTracker and Dazl, we confirmed the sturgeon BB/MC distribution in the cytosolic of early developing oocytes and partial co-localization with dazl.…”
Section: Discussionmentioning
confidence: 69%
“…Bars (a, d) 50 μm, (b, e) 20 μm shown that dazl RNA of Xenopus (Chang et al 2004), zebrafish (Kosaka et al 2007), gible carp (Peng et al 2009), medaka (Xu et al 2009) and trout (Li et al 2011) are concentrated within the BB/MC, a spherical-shaped structure. Nonetheless, in Acipenser gueldenstaedtii (Zelazowska et al 2007), oocytes contain two different zones of cytoplasm, the homogeneous ooplasm and granular ooplasm, with the granular ooplasm corresponding to the BB/MC. In sharp contrast to Xenopus and teleost BB/MC, by electron microscopy, in situ hybridization and immunostaining (Zelazowska et al 2007), the BB/MC surrounds the germinal vesicle and homogeneous ooplasm distributes in the oocyte periphery at stage I.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the first phase of oocyte development, numerous types of RNA and many other macromolecules are synthesized and localized into the specific regions of the oocyte cytoplasm. They are involved in the deposition of maternal determinants and the patterning of the embryo (Howley and Ho 2000;Żelazowska et al 2007). Previtellogenic oocytes exhibit essential changes in the organization of the nucleus, i.e., the germinal vesicle (GV), and cytoplasm.…”
Section: Introductionmentioning
confidence: 99%